Learners’ Perception To Use Media Podcasts In Vocabulary Learning - Juliandani, Astri; Suryaman, Maman; Kamil, Acep Bahrum (Peneliti.net, 2023)
The progress of the internet is the formation of new digital media that offers convenience, with podcasts for students who do not like to read and lack literacy which will be very helpful and very easy to access because podcasts are media that use on-demand features that can be accessed anytime and anywhere without the need to read and only by listening. On the other hand, other researchers previously found that almost all students struggled with pronunciation, writing, spelling, and grammar, causing difficulties for students in learning vocabulary. This study aimed to investigate the perceptions of students of the Faculty of Education and Teacher Training at Singaperbangsa Karawang University on the use of podcasts as a medium in Vocabulary learning. Data was collected from questionnaires and interviews. This study uses a descriptive qualitative approach with inquiry narrative research. This study uses the thematic analysis data analysis theory from Braun and Clarke (2006) which consists of 6 stages.